World's end - Verrillo, Erica F. (Verrillo, Erica F. Phoenix rising trilogy, 2009)
Still not accustomed to her life as a princess, Elissa, learning on the eve of her fifteenth birthday that she is to be betrothed to a man of her father's choosing, runs away and, after many difficulties, reunites with her friends to finally fulfill the prophecy of the Phoenix.